The Legal Position of Notary Deed in Establishing Water-Using Farmers' Associations - Ardhea Safira Prawestri; Taufan Fajar Riyanto (Sultan Agung Notary Law Review, 2022)
The role of the Notary in the process of establishing the Association, among others, is to make a deed of Establishment of the Association and register it with the Ministry of Law and Human Rights if it is desired that the association is a legal entity. The existence of an authentic deed made by a notary is used to protect and guarantee the rights and obligations of the parties to the agreement. A normative juridical approach is used in this study, and is carried out by examining existing library materials. The results of this study are the legal position of a notary deed in the establishment of a water user farmer association in Semarang district is recognized by regulations, namely according to Act No. 16 of 2017 concerning Stipulation of Government Regulation in Lieu of Act No. 2 of 2017 concerning Amendments to Act No. 17 of 2013 concerning Social Organizations. The legal consequences that arise from the establishment of a notarized association of farmers using water will result in legal certainty for farmers in improving irrigation management independently, efficiently, and effectively.